Strategi Komunikasi Pemasaran dalam Meningkatkan Jumlah Siswa (Studi Kasus pada Bimbingan Belajar Bintang Solusi Mandiri Cabang Pinang, Jakarta) - Saktisyahputra Saktisyahputra (LUGAS Jurnal Komunikasi, 2018)
Non-formal institutions such as a tutorial should always be ready with the changes issued by the government in the field of education. It should also be ready to compete with other tutorial and schools who offer tutorial services. To the authors chose the title "Marketing Communication Strategy Training and Tutoring Institute (Bimbel Solusi) Bintang Solusi Mandiri Branch Cipinang to Increase the Number of Students". Basic Theory used in this research is the theory of Marketing Mix according to Kotler Keller and SWOT Analysis by Fred R David. The method used in this research is qualitative - interpretive using case studies. Results of this research is Communication Strategy Training Institute and Tutoring Bintang Solusi Mandiri Branch Cipinang month of August 2018, namely the Direct Selling to residential introduce Tutoring (Bimbel) Solution through brochures, presentation Bimbel Solusi for each class in the school - the school through brochures, Distribution the share of school construction amounted to Rp.50.000 / student who joined Bimbel Solusi Branch Cipinang, follow-up database of students in the school by telephone and short message service (SMS) and then factor - a factor which supports the Institute for Training and Tutoring Bintang Solusi Mandiri Branch Cipinang in the areas of Strategy MarketingCommunication to increase the number of students is a factor of the program.